Efficacy of aminophylline vs. caffeine for preventing apnea of prematurity - Hendy Hendy; Setya Wandita; I Made Kardana (Indonesian Pediatric Society, 2014)
Background Apnea of prematurity (AOP) usually occursin neonates with a gestational age < 34 weeks. The WorldHealth Organization has recommended the administration ofcaffeine or aminophylline to prevent AOP, but the efficacy ofaminophylline remains unclear, and caffeine citrate is not availablein Indonesia.Objective To compare the efficacy of aminophylline to that ofcaffeine for preventing AOP.Methods This single-blind, clinical trial was conducted onneonates (gestational age 28-34 weeks) who were able to breathespontaneously within the first 24 hours of life and admitted toSanglah Hospital from December 2012 to April 2013. Subjectswere randomly allocated into two groups, namely groups ofaminophyllin and caffeine. The aminophylline group receivedaminophylline dihydrate at an initial dose of 10 mg/kg body weight,then continued with a maintenance dose of 2.5 mg/kg body weightevery 12 hours. The caffeine group received anhydrous caffeineat an initial dose of 10 mg/kg body weight, then continued witha maintenance dose of 1.25 mg/kg body weight every 12 hours.We followed subjects up until they were 10 days old. Subjectsreceived per oral therapy for seven days. The efficacy comparisonbetween the two groups was assessed by Chi-square test with 95%confidence interval (CI) and a statistical significance value of P< 0.05. We used multivariate test to analyze the confoundingfactors.Results Ninety-six subjects participated in this study; 48 subjectsreceived aminophylline therapy and the other 48 subjects receivedcaffeine therapy. Twenty-eight subjects experienced apnea: 13subjects from the aminophylline group (27.1%), and 15 subjectsfrom the caffeine group (31.3%). It appeared that aminophyllinewas slightly better compared to caffeine, but the difference wasnot statistically significant, with a relative risk of 0.9 (95% CI0.5 to 1.3; P=0.8). We found vomiting to be a side effect of boththerapies, and not significantly different between groups. SepsisFrom the Department of Child Health, Udayana University MedicalSchool/Sanglah Hospital, Denpasar1 and Gadjah Mada University MedicalSchool/Sardjito Hospital, Yogyakarta2.Reprint requests to: Hendy, Department of Child Health, UdayanaUniversity Medical School, Sanglah Hospital, Jl. Pulau Nias, Denpasar,Bali 80114. Tel./Fax: +62-361-244038. E-mail: hendyhalim.md@gmail.com.Infant prematurity is defined as a gestationalage of < 37 weeks. Africa has the highest birthrate of premature infants of 11.9%, while thatof Southeast Asia is approximately 11.1%.1The main issue that premature infants face is apnea.Apnea is caused by incomplete development ofthe respiratory center, and is known as apnea ofprematurity (AOP). Several factors underlie thenecessity of AOP prevention: an 85% incidence ofAOP in infants with gestational age <34 weeks,2difficulty in diagnosing AOP, unpredictable onset,short- and long-term effects, long treatment lengthand requirement of intensive care. The World Healthand hyaline membrane disease were found to be confoundingfactors in this study.Conclusion Aminophylline and caffeine have similar efficacywith regards to preventing AOP.